Analisis Perencanaan Bendung (Studi Kasus Bendung Botung) - Sadewa Sabihi; Manyuk Fauzi; Siswanto Siswanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This research will discuss the analysis of the stability of the dam in the area Botung against weir botung in the area Botung it self actually has no weir bronjong but the dam is temporary and has damaged it needs to be made weir remains to be utilized in the long term, so it takes the design of the lighthouse and the pool megrim secure against rolling, sliding and piping. Based on the results of the discussion of final project study entitled "Analysis weir Planning Case of Studies weir Botung" it can be concluded, using data of rain 10 Years of 2005-2014 years gained 100 year flood discharge plan for, Q100= 16.617 m3/sec. High water levels in the upstream dam is 2,456 m, and the water level downstream of the weir is 0.673 m, while the weir height following the existing dam is not fixed in the amount of 1,35m. And the dimensions of the flood discharge obtained value Froude of 7.632, and been building an megrim type USBR of type III. Safety Factor Values sliding obtained a value of 1.74 ≥1.5 and qualify. Safety Factor Values rolling obtained a value of 2.10 ≥1.5 and qualify. Planning this dam safe against piping for WCR value of 4.145 which is secure against gravel and clay.Keywords: weir, Curved tile, stability of the dam, rolling, sliding and piping